Espatolino - Gómez de Avellaneda, Gertrudis, 1814-1873. (Barcelona : www.Linkgua.com, 2019)
Espatolino is a villain who acts in Naples and Rome. Agents and spies have kept abreast of government and police movements, as well as the routes of travelers. Espatolino is agile and skillful with weapons. His name is a legend. But one day he meets a beautiful woman: Anunziata. From that moment on things changed within the gang and within Espatolino himself, who faces opposition from a new threat.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Recurso electrónico. Santa Fe, Arg.: elibro, 2021. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Cuban literature; Novela cubana; Libros electrónicos.